A case of paroxysmal kinesigenic dyskinesia which exhibited the phenotype of anxiety disorder - Kunii Y (Dove Medical Press, 2017)
Yasuto Kunii,1,2 Nozomu Matsuda,3 Hirooki Yabe1 1Department of Neuropsychiatry, Fukushima Medical University School of Medicine, Fukushima, Japan; 2Department of Neuropsychiatry, Aizu Medical Center, School of Medicine, Fukushima Medical University, Fukushima, Japan; 3Department of Neurology, Fukushima Medical University School of Medicine, Fukushima, Japan Background: Paroxysmal kinesigenic dyskinesia (PKD) is a rare heritable neurologic disorder characterized by attacks of involuntary movement induced by sudden voluntary movements. No previous reports have described cases showing comorbidity with psychiatric disease or symptoms. In this case, we showed a patient with PKD who exhibited several manifestations of anxiety disorder.Case: A 35-year-old Japanese man with PKD had been maintained on carbamazepine since he was 16 years of age without any attacks. However, 10 years before this referral, he became aware of a feeling of breakdown in his overall physical functions. He had then avoided becoming familiar with people out of concern that his physical dysfunctions might be perceived in a negative light. One day he was referred by the neurologic department at our hospital to the Department of Psychiatry because of severe anxiety and hyperventilation triggered by carbamazepine. We treated with escitalopram, aripiprazole, and ethyl loflazepate. Both his subjective physical condition and objective expressions subsequently showed gradual improvement. At last, the feelings of chest compression and anxiety entirely disappeared. Accordingly, increases in plasma monoamine metabolite levels were observed, and the c.649dupC mutation, which has been found in most Japanese PKD families, was detected in his proline-rich transmembrane protein 2 gene.Conclusion: This is the first report to describe psychiatric comorbidities or symptoms in a PKD case. The efficacy of psychotropic medication used in this case, the resulting changes in plasma monoamine metabolite levels, and the recent advances in the molecular understanding of PKD suggested slight, but widespread alterations to the neurotransmitter systems in the brain. Keywords: paroxysmal kinesigenic dyskinesia, anxiety disorder, proline-rich transmembrane protein 2, synaptosomal-associated protein 25